Associations between genetic variants in sphingolipid metabolism pathway genes and hepatitis B virus-related hepatocellular carcinoma survival - Jiang, Binbin; Qiu, Moqin; Qin, Liming; Tang, Jingmei; Zhan, Shicheng; Lin, Qiuling; Wei, Junjie; Liu, Yingchun; Zhou, Zihan; Liang, Xiumei; Cao, Ji; Lian, Jiawei; et al. (Frontiers in Oncology, 2024)
Although the sphingolipid metabolism pathway is known to play a significant role in tumor progression, there have been few studies on how genetic variants in the sphingolipid metabolism pathway genes affect the survival of patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC).We utilized available genotyping data to conduct multivariate Cox proportional hazards regression model analysis, examining the associations of 12,188 single nucleotide polymorphisms (SNPs) in 86 sphingolipid metabolism pathway genes on the survival of 866 HBV-HCC patients, and the model was also used in additive interaction analysis. We used bioinformatics functional prediction and expression quantitative trait locus (eQTL) analysis to explore the potential functions of SNPs and to evaluate the association of SNPs with the corresponding mRNA expression, respectively. We also used the online database TIMER2.0 (http://timer.comp-genomics.org/) to analyze the relationship between the corresponding mRNA expression levels and immune cell infiltration.Our study found that GBA2 rs1570247 G>A was significantly associated with elevated survival of HBV-HCC patients [(hazards ratio (HR)=0.74, 95% confidence interval (CI)=0.64-0.86, P<0.001)]. And on an additive scale, a synergistic effect was observed between the GG genotype of rs1570247 and advanced BCLC stage. Among HBV-HCC patients with advanced BCLC stage, those carrying the GBA2 rs1570247 GG genotype exhibited a significantly elevated risk of mortality (HR=3.32, 95%CI=2.45-4.50). Further functional prediction and eQTL analysis revealed that rs1570247 were located in the 5' untranslated region of the GBA2, the A allele of SNP rs1570247 was associated with higher mRNA expression levels of GBA2 in normal liver tissues (P=0.009). Moreover, we observed a positive correlation between GBA2 mRNA expression and the infiltration level of B lymphocytes cell (R=0.331, P<0.001), while a negative correlation was noted between GBA2 mRNA expression and the infiltration level of macrophage M2 in HCC (R=-0.383, P<0.001).3Our findings suggest that GBA2 rs1570247 G>A in sphingolipid metabolism pathway may be a key factor for survival of HBV-HCC patients by regulating the expression of corresponding genes and affecting the infiltration level of immune cells.